2007
DOI: 10.1093/brain/awm126
|View full text |Cite
|
Sign up to set email alerts
|

Primary episodic ataxias: diagnosis, pathogenesis and treatment

Abstract: Primary episodic ataxias are autosomal dominant channelopathies that manifest as attacks of imbalance and incoordination. Mutations in two genes, KCNA1 and CACNA1A, cause the best characterized and account for the majority of identified cases of episodic ataxia. We summarize current knowledge of clinical and genetic diagnosis, genotype-phenotype correlations, pathophysiology and treatment of episodic ataxia syndromes. We focus on unresolved issues including phenotypic and genetic heterogeneity, lessons from an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
339
3
11

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 341 publications
(359 citation statements)
references
References 70 publications
6
339
3
11
Order By: Relevance
“…EA2 is a dominantly inherited disorder characterized by paroxysmal disturbance of the cerebellar-brainstem circuitry manifesting as attacks of ataxia, vertigo, vomiting, and nystagmus (Jen et al 2004(Jen et al , 2007. The prevalence of epilepsy (Rajakulendran et al 2010) and EEG abnormalities (Neufeld et al 1996) in individuals with clinical and genetically confirmed EA2 is higher than the background population, suggesting that genetic variations in CACNA1A may be a potential susceptibility factor in human epilepsy.…”
Section: Dominant Mutations In Ca V 21 Cause Episodic Ataxia Typementioning
confidence: 99%
“…EA2 is a dominantly inherited disorder characterized by paroxysmal disturbance of the cerebellar-brainstem circuitry manifesting as attacks of ataxia, vertigo, vomiting, and nystagmus (Jen et al 2004(Jen et al , 2007. The prevalence of epilepsy (Rajakulendran et al 2010) and EEG abnormalities (Neufeld et al 1996) in individuals with clinical and genetically confirmed EA2 is higher than the background population, suggesting that genetic variations in CACNA1A may be a potential susceptibility factor in human epilepsy.…”
Section: Dominant Mutations In Ca V 21 Cause Episodic Ataxia Typementioning
confidence: 99%
“…In vivo and in vitro tests herein indicated the decrease in CACNA1A expression upon AgNPs treatment, showing the inhibition of Cav2.1 channel was involved in AgNPs-mediated cerebellar ataxia-like neurobehavior. Although the dysfunction of voltage-gated potassium channel (Kv1.1 channel) could be associated with the cerebellar ataxia as well (Jen et al, 2007), no alteration was observed in the level of Kv1.1 channel protein upon AgNPs treatment, indicating that voltage-gated potassium channel was not related with AgNPs-induced cerebellar ataxia-like symptom.…”
Section: Discussionmentioning
confidence: 99%
“…Characterized by the impaired coordinate balance, cerebellum ataxia is a non-specific clinical manifestation implying partial dysfunction of the nervous system that coordinates movement, such as the cerebellum (Schmahmann, 2004). Mounting evidences have given some important clues to pathogenic mechanisms in cerebellum ataxia, such as disruption of voltage-gated potassium and calcium channels (Jen et al, 2007;Mori et al, 1991). Our previous study found that AgNPs exposure could attenuate the viability of rat cerebellum granule cells (CGCs) through apoptosis (Yin et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These mutations often predict a premature stop due to defect on the splice site or are nonsense mutations. EA2 responds to acetazolamide [1][2][3]. This man presented with EA2 caused by a novel single base insertion that predict the expression of a truncated CACNA1A protein.…”
Section: Introductionmentioning
confidence: 99%
“…EA2, SCA6, and FHM1 are all allelic disorders of the same CACNA1A gene [3]. SCA6 presents with a late-onset slowly progressive pure cerebellar disorder ataxia [4], differentiating it from EA2.…”
Section: Introductionmentioning
confidence: 99%